Revisiting English language proficiency and its impact on the academic performance of domestic university students in Singapore. (January 2023) - Bo, Wenjin Vikki; Fu, Mingchen; Lim, Wei Ying
The role of international students' English language proficiency has been extensively researched to understand its impact on academic achievement in English-medium universities, mainly because of students' non-English-speaking backgrounds. However, the relationship between language proficiency and academic achievement among English-speaking-background students remains under-researched, especially in multilingual societies, such as Singapore. The present study explored the relationship among university students' previous academic experience, English language proficiency, and their current academic performance within a sample of 514 Singaporean students (252 females and 262 males). Findings showed that students' proficiency scores significantly predicted their current grade point average (GPA) with their prior academic performance being controlled. Moreover, proficiency scores significantly strengthened the association between students' prior academic performance and their current GPA. Finally, academic discipline showed a marginally significant moderating effect in the relationship between proficiency scores and current GPA. Implications and limitations of the study are discussed.